Assembly mechanism of primary forest dominated by habitat filtering in karst degradation region - Sun, Wenhui; Yang, Lili; Zhang, Chen; He, Gongxiu; Du, Hu; Zeng, Zhaoxia; Zhang, Hao (Frontiers in Plant Science, 2025)
IntroductionThe revelation of the assembly mechanism of plant communities in karst region has crucial implications for the restoration of degraded vegetation. Niche theory and neutral theory are the two main theories to elucidate community assembly of karst plant community. However, the relative significance of habitat filtration and biological action in community assembly remains a topic of debate.MethodsBy using measurement of plant functional traits, detection of phylogenetic signal (K value), and average shared variance, our investigation aimed to ascertain whether species coexistence in community assembly of primary forest is driven by habitat filtering or biotic constraints.ResultsIn all 10 plant functional traits, leaf carbon (LC) had the lowest variation coefficient, whereas leaf area (LA) exhibited the highest. Significant phylogenetic signals (P < 0.05) were identified for plant LC, LA, wood density (WD), leaf nitrogen (LN) and leaf phosphorus (LP). Phylogenetic signal strength (K < 1) of all traits indicated that the phylogenetic conservation of functional traits is relatively weak and may be influenced by environmental screening or convergent evolution. Both the phylogenetic net relatedness index (NRI) and nearest taxon index (NTI) were negative, indicating a divergent phylogenetic structure. Additionally, with the exception of LA and leaf length-width ratio (L/D), the mean pairwise trait distance indices (SES.PW) were greater than 0, suggesting a tendency towards aggregation in the functional trait structure. Furthermore, average shared variance demonstrated that variation in plant functional trait was predominantly influenced by soil fertility and topography of the sample DiscussionOur finding indicated that the community assembly of primary forest plant was dominated by habitat filtering, which could significantly promote a more profound comprehension of natural restoration in karst degradation region.